COVID-19, Indigenous peoples, local communities and natural resource governance - Walters, G.; Broome, N.P.; Cracco, M.; Dash, T.; Dudley, N.; Elías, S.; Hymas, O.; Mangubhai, S.; Mohan, V.; Niederberger, T.; Nkollo-Kema Kema, C.A.; Oussou Lio, A.; et al. (International Union for Conservation of Nature, 2021)
We report on how the COVID-19 pandemic is affecting Indigenous peoples and local communities (IPLCs), especially those who govern, manage and conserve their lands and waters. We explore the themes of access and use of natural resources, solidarity, decision-making, the role of governments and IPLCs in managing COVID-19, and the uptake of traditional medicine. These themes are explored through a global online survey in English, Spanish and French. We collected and analysed 133 surveys from 40 countries, using SenseMaker®, a software that enables analysis of micronarratives based on how respondents classify their own stories. We explore the themes further through case studies from Benin, Fiji, France, Gabon, Guyana, Guatemala, India and Madagascar, highlighting challenges and opportunities in how IPLCs responded to COVID-19. Our study underscores the importance of selfempowerment and recognition of IPLC rights, which allows them to use traditional medicines, meet subsistence requirements during lockdowns, help community members and neighbours to sustain livelihoods, and to govern, defend and conserve their territories. We propose key actions to support IPLCs navigate future pandemics while protecting their lands and waters.